2020
DOI: 10.1007/s12630-020-01584-w
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hunger after outpatient surgery in patients anesthetized with propofol vs sevoflurane: a randomized-controlled trial

Abstract: Previous preclinical and preliminary clinical data suggest an appetite-stimulating effect of propofol compared with halogenated drugs. This study compared the effects of propofol with those of sevoflurane on recovery of hunger during the postoperative period. Methods Patients undergoing outpatient transvaginal oocyte retrieval were randomized to propofolremifentanil (propofol group) or sevoflurane-remifentanil (sevoflurane group) anesthesia. The primary endpoint was the time before feeling hungry (C 50/100 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…3E). The decrease in ghrelin observed in the sham group could be due to effects of inhaled anesthetics and endoscopic intervention, consistent with previously published findings ( 18 21 ).…”
Section: Resultssupporting
confidence: 92%
“…3E). The decrease in ghrelin observed in the sham group could be due to effects of inhaled anesthetics and endoscopic intervention, consistent with previously published findings ( 18 21 ).…”
Section: Resultssupporting
confidence: 92%
“… 37 , 41 Previous study done in France has shown that, compared with sevoflurane, propofol did not accelerate the recovery of appetite after outpatient minor surgery. 42 Furthermore, propofol had no influence on other clinical or biological markers connected with food intake.…”
Section: Discussionmentioning
confidence: 96%
“…We read with interest the report of the recent randomized-controlled trial conducted by Besnier et al 1 In this study, the authors compared the effects of propofol and sevoflurane on postoperative hunger in outpatients undergoing transvaginal oocyte retrieval and showed that propofol did not promote recovery of hunger. We would like to put forward some potential limitations in their study related to their statistical handling of the data.…”
Section: To the Editormentioning
confidence: 99%